2015
DOI: 10.1111/dom.12503
|View full text |Cite
|
Sign up to set email alerts
|

Impact of empagliflozin added on to basal insulin in type 2 diabetes inadequately controlled on basal insulin: a 78‐week randomized, double‐blind, placebo‐controlled trial

Abstract: Aims:To investigate the efficacy and tolerability of empagliflozin added to basal insulin-treated type 2 diabetes. Methods: Patients inadequately controlled [glycated haemoglobin (HbA1c) >7 to ≤10% (>53 to ≤86 mmol/mol)] on basal insulin (glargine, detemir, NPH) were randomized to empagliflozin 10 mg (n = 169), empagliflozin 25 mg (n = 155) or placebo (n = 170) for 78 weeks. The baseline characteristics were balanced among the groups [mean HbA1c 8.2% (67 mmol/mol), BMI 32.2 kg/m 2 ]. The basal insulin dose was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
222
1
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(251 citation statements)
references
References 37 publications
(46 reference statements)
20
222
1
8
Order By: Relevance
“…110 However, in the EMPA-REG BASAL (Impact of empagliflozin added on to basal insulin in type 2 diabetes inadequately controlled on basal insulin) study, which enrolled patients with type 2 diabetes with BMI ≤ 45 kg/m 2 , inadequately controlled (HbA 1c > 7% to ≤ 10%), despite treatment with basal glargine or detemir insulin (≥ 20 IU/day) or NPH insulin (≥ 14 IU/day), with or without metformin and/or sulfonylurea use, Rosenstock et al 111 observed that both UTIs as well as GTIs were more frequent in the empagliflozin groups than with the placebo group.…”
Section: Empagliflozinmentioning
confidence: 99%
“…110 However, in the EMPA-REG BASAL (Impact of empagliflozin added on to basal insulin in type 2 diabetes inadequately controlled on basal insulin) study, which enrolled patients with type 2 diabetes with BMI ≤ 45 kg/m 2 , inadequately controlled (HbA 1c > 7% to ≤ 10%), despite treatment with basal glargine or detemir insulin (≥ 20 IU/day) or NPH insulin (≥ 14 IU/day), with or without metformin and/or sulfonylurea use, Rosenstock et al 111 observed that both UTIs as well as GTIs were more frequent in the empagliflozin groups than with the placebo group.…”
Section: Empagliflozinmentioning
confidence: 99%
“…1), totalling 15,309 unique participants [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Four SGLT2 inhibitors (canagliflozin, dapagliflozin, empagliflozin and ipragliflozin) were evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Empagliflozin has consistently been shown to lead to sustained weight loss in patients with type 2 diabetes 13, 14, 15, 16, 17, 18, including those treated with a regimen of multiple daily injections of insulin, likely due to loss of calories in the urine. The majority of weight loss in patients with type 2 diabetes is attributable to a reduction in fat mass, including reductions in both trunk fat and limb fat and in both abdominal visceral and abdominal subcutaneous adipose tissue 23.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with type 2 diabetes, empagliflozin given as monotherapy or as add‐on therapy (including as add‐on to basal insulin or multiple daily injections of insulin) has consistently been shown to improve glycaemic control and reduce blood pressure and weight, with a low risk of hypoglycaemia 13, 14, 15, 16, 17, 18.…”
Section: Introductionmentioning
confidence: 99%